1991
DOI: 10.1159/000186649
|View full text |Cite
|
Sign up to set email alerts
|

Blood and Urinary Aggregator and Inhibitor Composition in Controls and Renal-Stone Patients from Northeastern Thailand

Abstract: Renal-stone disease (RSD) is common in the rural communities of northeastern Thailand. We report the biochemical composition of blood and urine in 25 healthy city dwellers (Gl), 12 healthy village dwellers (G2) and 25 village dwellers who had RSD (G3). They were male with a range of ages between 20 and 50 years and were free of renal failure, urinary infection, urinary obstruction and systemic illness. The results showed that hypocitraturia, hypokalemia and hypokaliuria were more common in the latter 2 groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 23 publications
3
29
1
Order By: Relevance
“…It could be found among healthy rural dwellers, renal stone formers [9] and patients with distal renal tubular acidosis [22]. Hypokalemia and low urinary potassium excretion can be corrected with potassium supplementation suggesting that there was potassium deficiency [10], The mechanism of potassium depletion is not fully understood and might be multifactorial. The dietary potassium intake of NorthEast Thais can be as low as 20-25 mmol/dav [Puwasatien et al, pers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be found among healthy rural dwellers, renal stone formers [9] and patients with distal renal tubular acidosis [22]. Hypokalemia and low urinary potassium excretion can be corrected with potassium supplementation suggesting that there was potassium deficiency [10], The mechanism of potassium depletion is not fully understood and might be multifactorial. The dietary potassium intake of NorthEast Thais can be as low as 20-25 mmol/dav [Puwasatien et al, pers.…”
Section: Discussionmentioning
confidence: 99%
“…These hypotheses are, however, difficult to prove when the subjects are still alive since SUDS is a retrospective diagnosis. We have pre viously reported that hypokalemia and low urinary potas sium are common in healthy rural males from North-East Thailand [10]. Moreover, this population group also had lower activity of erythrocyte membrane Na,K-ATPase and higher erythrocyte sodium (RBCNa) than Thais from other regions of the country [11], Since SUDS victims from North-East Thailand are healthy prior to death, they might have similar metabolic abnormalities.…”
mentioning
confidence: 99%
“…Furosemide is reported to affect renal excretion of several ions such as sodium, potassium, magnesium, which in turn may affect citrate excretion [22,27,33]. A study with non-furosemide treated infants demonstrated differences in urinary excretion of the above minerals that could be attributed to the different type of feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Dear Sir, Sriboonlue et al [ 1 ] have found a relation ship between citraturia and kaliuria among stone formers. Their patients were village dwellers whose urinary and blood analysis show ed a potassium deficiency co m p ared to nonstone formers living in a large city.…”
mentioning
confidence: 99%
“…Cotransport was stimulated and citrate reabsorption was increased with hypo citraturia. Sriboonlue et al [1] said excessive sweat and dietary factors could be the cause of potassium depletion. They administered potassium chloride to their patients and ob tained a correction of potassium depletion without hypocitraturia modification.…”
mentioning
confidence: 99%